Neurodegenerative diseases and blood pressure variability: A comprehensive review from HOPE Asia - Turana, Yuda; Shen, Robert; Nathaniel, Michael; Chia, Yook Chin *; Li, Yan; Kario, Kazuomi (Wiley, 2022)
Asia has an enormous number of older people and is the primary contributor to the rise in neurodegenerative diseases such as Alzheimer's and Parkinson's disease. The therapy of many neurodegenerative diseases has not yet progressed to the point where it is possible to alter the course of the disease. Mid-life hypertension is an important predictor of later-life cognitive impairment and brain neurodegenerative conditions. These findings highlight the pivotal role of preventing and managing hypertension as a risk factor for neurodegenerative disease. Autonomic dysfunction, neuropsychiatric and sleep disturbances can arise in neurodegenerative diseases, resulting in blood pressure variability (BPV). The BPV itself can worsen the progression of the disease. In older people with neurodegenerative disease and hypertension, it is critical to consider 24-h blood pressure monitoring and personalized blood pressure therapy.